2021
DOI: 10.1177/10711007211010188
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study Comparing Functional Outcomes of Primary and Revision Ankle Replacements

Abstract: Background: The number of ankle and revision ankle replacements performed is increasing. There is limited research into functional outcomes, especially in revision ankle replacements. The primary aim of this cohort study was to determine the functional improvements following primary and revision ankle replacements and compare which gave the greatest improvement in functional scores. Methods: A single-center prospective cohort study was undertaken between 2015 and 2018. All patients were followed up for a minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…17,18 As surgical techniques and implant design continually improve, so has implant survivorship, with recent midterm studies demonstrating survival rates ranging from 80% to 98%. 13,15,25,40 Early results from modern implants have demonstrated that TAA is equivalent to arthrodesis in terms of relieving pain, but result in improved functional outcomes, 20,41 with a systematic review suggesting that TAA is associated with fewer complications and higher reoperation rates. 29 In addition, a previous report has demonstrated that TAA offers advantages of preserving range of motion and allowing for gait patterns that are more physiologic compared to patients with an ankle arthrodesis.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 As surgical techniques and implant design continually improve, so has implant survivorship, with recent midterm studies demonstrating survival rates ranging from 80% to 98%. 13,15,25,40 Early results from modern implants have demonstrated that TAA is equivalent to arthrodesis in terms of relieving pain, but result in improved functional outcomes, 20,41 with a systematic review suggesting that TAA is associated with fewer complications and higher reoperation rates. 29 In addition, a previous report has demonstrated that TAA offers advantages of preserving range of motion and allowing for gait patterns that are more physiologic compared to patients with an ankle arthrodesis.…”
Section: Introductionmentioning
confidence: 99%
“…for primary TAAs compared with 20.2 for revision TAAs, which was a statistically significant difference. 9 In the revision TAA cohort, the 6 patients who underwent a 2-stage septic revision arthroplasty had, on average, less improvement in their MOxFQ scores than those patients who underwent an aseptic revision although this did not reach statistical significance. 9 Sangeorzan et al recently demonstrated statistical and clinical improvement in patient-reported outcomes following primary TAA and ankle arthrodesis using the FAAM ADL and Sports subscales.…”
Section: Discussionmentioning
confidence: 87%
“…25 Recent studies have demonstrated that improvements in patient-reported outcomes following a revision TAA are significantly lower than those following a primary TAA. 9 Jennison et al reported that the mean overall change in the Manchester Oxford Foot Questionnaire (MOxFQ) was 48.8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 41 The Swedish Arthroplasty Registry reports a mean SEFAS score of 22 after revision ankle arthroplasty compared to 31 after primary arthroplasties, and this was also found by Lachman et al 6 across all scores. 41 , 43 The only study that directly compares functional scores between revision arthroplasty and conversion to fusion demonstrates similar functional scores for both techniques. 5 , 8 A greater proportion of outcome scores were significantly improved with revision ankle arthroplasty than conversion to fusion, but due to small numbers it was impossible to calculate if this was statistically significant.…”
Section: Discussionmentioning
confidence: 99%